Assessing the vulnerability of logistics service supply chain based on complex network - Ma, Fei (2021)
The reliable operation of a logistics service supply chain (LSSC) is a key factor for improving logistics efficiency and service level, and vulnerability is an important indicator of reliable LSSC operation. Based on complex network theory, we reconstructed the running mechanism of logistics service providers, integrators, and demanders. We constructed an improved structure model of LSSC. By observing the selected three indicators (clustering coefficient, maximum connectivity, and network connectivity efficiency), the influence caused by the problem will continue to spread to more subjects along the network when a problem exists in one part of the network. The results showed that the destructive power of deliberate attacks is far greater than the damage caused by random attacks, and the disruption of logistics service integrators will considerably increase the vulnerability of the LSSC. However, even if logistics service integrators are removed completely, the LSSC still can operate at low efficiency. Through a case analysis, we identified the vulnerable nodes in logistics service, clarify the vulnerable mechanism in LSSC, and provide guidance for the operation of LSSC in real life.